2009
DOI: 10.1203/pdr.0b013e3181b1bbec
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Partial Aldosterone Resistance in Human Newborns

Abstract: ABSTRACT:In the neonatal period, the human kidney is characterized by an impaired ability to regulate water and sodium homeostasis, resembling partial aldosterone resistance. The aim of our study was to assess this hormonal insensitivity in newborn infants and to determine its relationship with neonatal sodium handling. We conducted a prospective study in 48 healthy newborns and their mothers. Aldosterone, renin, and electrolyte concentrations were measured in umbilical cords and in maternal plasma. Urinary al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
70
1
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(81 citation statements)
references
References 35 publications
4
70
1
3
Order By: Relevance
“…After the period of physiologic aldosterone resistance (20), each individual presented with life-threatening salt-loss within the second week of life. In most patients, CAH was initially suspected as it is the most common cause of neonatal onset of salt-losing crisis.…”
Section: Discussionmentioning
confidence: 99%
“…After the period of physiologic aldosterone resistance (20), each individual presented with life-threatening salt-loss within the second week of life. In most patients, CAH was initially suspected as it is the most common cause of neonatal onset of salt-losing crisis.…”
Section: Discussionmentioning
confidence: 99%
“…In the newborn period, the fetal adrenal gland is proportionally bigger and more active that adult adrenal gland, but it regresses from the sixth month after birth, which is consistent with a partial aldosterone resistance at this early stage of life. 32,33 The transition zone occurs at the glomerular and fascicular layers that produce aldosterone and cortisol, respectively. These zones are fully developed at the age of Ϸ3 years.…”
Section: Discussionmentioning
confidence: 99%
“…These authors found that in a population of 48 term neonates urinary aldosterone, unlike plasma aldosterone, was significantly and negatively correlated to the plasma potassium, leading to the conclusion that aldosterone participates in the control of potassium balance and that determination of urinary aldosterone levels constitutes an interesting non-invasive method to investigate aldosterone sensitivity in preterm and full-term infants. 19 In the neonatal period, several clinical and biochemical variables, such as gestational age, birth weight, plasma electrolytes, drugs and degree of illness, may interfere with aldosterone production.…”
Section: Discussionmentioning
confidence: 99%